α-C–H Photoalkylation of a Glucose Derivative in Continuous Flow - Mouthaan, Marc L. M. C.; Pouwer, Kees; Borst, Mark L. G.; Witte, Martin D.; Minnaard, Adriaan J. (Synthesis, 2022)
Site-selective photoalkylation is a powerful strategy to extend the carbon framework of carbohydrates, otherwise often attainable only through laborious syntheses. This work describes the adaptation and upscaling of the photoalkylation of a glucose derivative as a continuous flow process. The reported iridium catalyst is replaced by an organic sensitizer and the reaction has been carried out on 40-gram scale.
Keywords: C–H functionalization; photoredox catalysis; carbohydrates; flow chemistry; hydrogen atom transfer; radicals